Grammar review for the Toefl = Ôn tập ngữ pháp cho bài thi Toefl - Murphy, Andrew F. (Nxb Tp.HCM, 1997)
Review of grammar and syntax; Punctuation, capitalization, anh abbreviations; Review of english usage.